Segmentasi Pasar Pariwisata Provinsi Jawa Barat Menggunakan K-Means Berdasarkan Jumlah Kunjungan, Hotel, dan Restoran - Difa Pratama Hakim; Safrizal Safrizal (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
This study was conducted with the aim of segmenting tourism in the West Java Province to help local governments to identify the characteristics and potential of each region in order to determine more targeted development strategies. The approach used is K-Means Clustering with variables of the number of visits, restaurants, and hotels with the data period used from 2021 to 2024. The analysis process carried out includes data normalization, determining the optimal cluster value with the Elbow Method and Silhouette Score, then visualizing the clustering results with PCA and geospatial maps. The resulting clustering shows two main clusters: clusters with high infrastructure and number of tourists (such as Bandung City and Bogor Regency) and clusters with tourism potential that still need more attention. The conclusion of this study successfully answers the objectives and contributions of the research to be achieved, that the approach used can reveal the inequality of potential in each region and provide a picture of data-based development priorities.